Consensus on the Clinical Approach to Moderate-to-Severe Atopic Dermatitis in Spain: A Delphi Survey - Joaquín Sastre; Esther Serra Baldrich; José Carlos Armario Hita; L. Herráez; Ignacio Jáuregui; Ana Martín-Santiago; Javier Ortiz de Frutos; Juan Francisco Silvestre; Antonio Valero (Hindawi Limited, 2020)
Background. The purpose of this study was to gather information on the current assessment and management of patients with moderate-to-severe AD in routine daily practice. Methods. A cross-sectional two-round Delphi survey with the participation of dermatologists and allergologists throughout Spain was conducted. They completed a 46-item questionnaire, and consensus was defined when responses of ≥80% of participants coincided in the categories of a 5-point Likert scale for that item. Results. A total of 105 specialists (aged 40-59 years) completed the two rounds. Participants agreed regarding the consideration of AD as a multifaceted disease and the differences in clinical presentation of AD according to the patient's age. It is recommendable to perform a skin biopsy to exclude early stage T-cell cutaneous lymphoma, psoriasis, or dermatitis herpetiformis, among others (99.1%). Also, consensus was reached regarding the use of the SCORAD index to quantify the severity of the disease (86.7%), the use of wet wraps to increase the effect of topical corticosteroids (90.4%), the usefulness of proactive treatment during follow-up (85.6%) and tacrolimus ointment (91.2%) to reduce new flares, and the fact that crisaborole is not the treatment of choice for severe AD (92.4%). AD was not considered a contraindication for immunotherapy in patients with allergic respiratory diseases (92.4%). In patients with severe AD, the use of immune response modifier drugs (97.6%) or phototherapy (92.8%) does not sufficiently cover their treatment needs. Consensus was also obtained regarding the role of the new biologic drugs (93.6%) targeting cytokines involved in the Th2 inflammatory pathway (92.0%) and the potential role of dupilumab as first-line treatment (90.4%) in moderate-to-severe AD patients. Conclusion. This study contributes a reference framework to the care of AD patients. There is no diagnostic test or biomarkers to direct treatment or to assess the severity of the disease, and many therapeutic challenges remain.